Effects of School Closures, 2008 Winter Influenza Season, Hong Kong - Benjamin J. Cowling; Eric H.Y. Lau; Conrad L.H. Lam; Calvin K.Y. Cheng; Jana Kovar; Kwok Hung Chan; J.S. Malik Peiris; Gabriel M. Leung (Emerging Infectious Diseases, 2008)
In winter 2008, kindergartens and primary schools in Hong Kong were closed for 2 weeks after media coverage indicated that 3 children had died, apparently from influenza. We examined prospective influenza surveillance data before, during, and after the closure. We did not find a substantial effect on community transmission.